The Moderating Effects of Age on the Relationships of Self‐Compassion, Self‐Esteem, and Mental Health. (5th February 2016) - Hwang, Soodeok; Kim, Geunyoung; Yang, Jae‐Won; Yang, Eunjoo
Abstract: This study investigated the interactive effects of self‐compassion, self‐esteem, and age on mental health. Numerous previous studies have found that self‐compassion has a significant positive association with well‐being but most of these studies were conducted with young adults represented by college students. This study extended the previous findings by comparing its distinctive functions in different age groups. A total of 1, 813 adults whose age ranged from twenties to fifties ( M  = 39.28 years, SD  = 11.27) completed a questionnaire measuring self‐compassion, self‐esteem, subjective well‐being, and depression. The results of hierarchical regression analysis indicated that the positive relationship between self‐compassion and subjective well‐being was rendered stronger with older adults. In addition, self‐compassion moderated the relationship between self‐esteem and depression regardless of age. These results imply that self‐compassion may be complimentary to self‐esteem in improving mental health, especially for older adults.